Innovative Approach to the Organization of the Educational Process - Nodira Kushakova; Shoira Kutbiddinova (Zien Journals, 2022)
This article is about issues on ways of improving the effectiveness in educational system-innovational approach, its appropriateness to modern demands of education - disciplineproduction and analyse of education quality is paid to interrelation of.
Keywords: education; technology; integrational